Glutaredoxin-1 Overexpression Enhances Neovascularization and Diminishes Ventricular Remodeling in Chronic Myocardial Infarction - Adluri, Ram Sudheer; Thirunavukkarasu, Mahesh; Zhan, Lijun; Dunna, Nageswara Rao; Akita, Yuzo; Selvaraju, Vaithinathan; Otani, Hajime; Sanchez, Juan A.; Ho, Ye-Shih; Maulik, Nilanjana (PLOS ONE, 2012)
Oxidative stress plays a critical role in the pathophysiology of cardiac failure, including the modulation of neovascularization following myocardial infarction (MI). Redox molecules thioredoxin (Trx) and glutaredoxin (Grx) superfamilies actively maintain intracellular thiol-redox homeostasis by scavenging reactive oxygen species. Among these two superfamilies, the pro-angiogenic function of Trx-1 has been reported in chronic MI model whereas similar role of Grx-1 remains uncertain. The present study attempts to establish the role of Grx-1 in neovascularization and ventricular remodeling following MI. Wild-type (WT) and Grx-1 transgenic (Grx-1Tg/+) mice were randomized into wild-type sham (WTS), Grx-1Tg/+ Sham (Grx-1Tg/+S), WTMI, Grx-1Tg/+MI. MI was induced by permanent occlusion of the LAD coronary artery. Sham groups underwent identical time-matched surgical procedures without LAD ligation. Significant increase in arteriolar density was observed 7 days (d) after surgical intervention in the Grx-1Tg/+MI group as compared to the WTMI animals. Further, improvement in myocardial functional parameters 30 d after MI was observed including decreased LVIDs, LVIDd, increased ejection fraction and, fractional shortening was also observed in the Grx-1Tg/+MI group as compared to the WTMI animals. Moreover, attenuation of oxidative stress and apoptotic cardiomyocytes was observed in the Grx-1Tg/+MI group as compared to the WTMI animals. Increased expression of p-Akt, VEGF, Ang-1, Bcl-2, survivin and DNA binding activity of NF-κB were observed in the Grx-1Tg/+MI group when compared to WTMI animals as revealed by Western blot analysis and Gel-shift analysis, respectively. These results are the first to demonstrate that Grx-1 induces angiogenesis and diminishes ventricular remodeling apparently through neovascularization mediated by Akt, VEGF, Ang-1 and NF-κB as well as Bcl-2 and survivin-mediated anti-apoptotic pathway in the infarcted myocardium.